Interpretation of the Verse of Polygamy (Comparative Study of Hermeneutics of Muhammad Abduh and Amina Wadud) - Kamaluddin (Penerbit Hellow Pustaka, 2025)
Polygamy is one of the topics that is still a topic of considerable interest among exegetes. The conversation about this hat has attracted a lot of attention, causing long discussions and debates using various methods. Among the exegetes who discuss this polygamy are Amina Wadud and Muhammad Syahrur. This research uses descriptive-analytical research to describe the data collected and make a literature study (Library Research) as a data source. Amina Wadud tends to reject polygamy with the argument that this practice is not in accordance with the concept of gender equality and does not support the formation of a loving family as expected by the Qur'an. Moreover, in his view, there is not a single verse in the Qur'an that explicitly supports the practice of polygamy. Meanwhile, Muhammad Abduh allows polygamy on condition that it is in an emergency, that is, if the benefits outweigh the harms.